Performance-Based Budgeting in the Public Sector (Public Sector Economics - submission site, 2020)
This book provides a comparative analysis of performance budgeting and financing implementation, and examines failures and successes across both developed and developing countries. Beginning with a review of theoretical research on performance budgeting and financing, the book synthesises the numerous studies on the subject. The book describes the situation in the US, Australia, New Zealand, Germany, Austria and Switzerland, Netherlands and Italy, as well as in seven developing countries - Bulgaria, Czech Republic, Slovakia, Slovenia, Ukraine, Russia and South Africa, at the national, and at the local level. Each chapter provides historical and descriptive details of successful or failed experiments in performance budgeting and performance financing.